Formación en lectura de cuentos: Impacto en intervenciones en educadoras docentes y no docentes - Manrique, María Soledad (Universidad de Costa Rica, 2019)
In order to study the changes that the training promotes, the research compares the impact of a formative   four months term project, in the interventions during the reading of stories by two educator groups of  infants living in poverty in Argentina : one  group of non-teaching educators,   other  of teacher educators. The non-teaching educators are five caregivers, with a low level of education and specific training of an informal nature. The teacher educators are 5 qualified teachers with several years exercising their role. Both groups of caregiver women for a child population from 3 to 5 years old from vulnerable sectors. The designed training device fulfilled a double objective of research and training. On the one hand, it allowed, to study the processes of change in the participants. On the other hand, it aimed to promote in the participants the development of skills which would rise a platform during the reading of stories that will enhance the linguistic and cognitive development of children. It had two samples: a group and an individual. The sample groups were developed through the workshop methodology with a series of activities such as follow: Dramatizations of reading situations, video visualisations of teachers reading stories, exhibitions in which new concepts were presented about children cognitive processes to understand a story and its difficulties and exercises that allowed to test possible ways of intervention to facilitate these processes. In the individual sample, a film was performed by each teacher reading a story and the filmed situation was transcribed then such situation was analyzed together with the teacher. The corpus was set up with the 10 situations of reading of previous stories (5 of each group of educators) and the 10 subsequent to the training device. The constant comparative method was used in the elaboration of a system by categories to classify the predications of the extra-textual speech of both groups of educators during the reading of stories, according to the demand of cognitive processing raised in each preaching. The obtained information allowed to codify the educators interventions . The results of the quantitative analysis in which the frequency of appearance of the analyzed categories is balanced in each situation, show important differences between both groups during the reading situations prior to the course. They also show how these differences in the intervention between both groups of educators are reduced after the training. These results were complemented by the description of the stories and the reading dynamics. We conclude that, while the increase in interventions with high cognitive demand for infants-observed in both groups is greater for non-teaching educators, the device seems to have had greater impact in this group than in the one of the teachers. We discuss the implications of this finding in terms of reading a story versus oral narration, and also in relation to the design of the training device, its transformative capacity and the conditions of possibility for training in all the persons.